When workers' skills become unbundled: Some empirical consequences for sorting and wages - Oskar Nordström Skans; Philippe Choné; Francis Kramarz (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2022)
This empirical paper analyzes labor market sorting across establishments using Swedish register data on cognitive and non-cognitive abilities. We draw on the theoretical foundations of Chone' and Kramarz (2021), in which workers are endowed with sets of multidimensional skills that need to be sold in "bundles" to employers that differ in their use of each of these skills. The theory also outlines how wage and sorting patterns should evolve when innovations "unbundle" the skills through the emergence of markets where each specific skill can be traded s eparately. Our empirical results show that labor is sorted across establishments on both comparative advantage and absolute ability. Furthermore, wage returns to each skill is higher in market segments where employers rely more heavily on workers who specialize in that particular skill. Changes over time are well in line with a process of unbundling; sorting on comparative advantage has increased and the market wages of generalists have risen relative to those of specialists.
Keywords: J23; J24; J31; 330; Cognitive skills; Non-Cognitive Skills; Firms; Technology